Customers as "partial" employees of organizations: good or bad?. Issue 10 (21st October 2019) - Zhuang, Weiling; Babin, Barry J.; Borges, Adilson
Abstract : Purpose: The purpose of this study is to address the following research questions: How do customer input and service provider (in this study, the terms firm and service provider are used interchangeably) input coproduce customer experience and response? Do different components of customer input influence customer experience differently? Design/methodology/approach: Structural equation modeling (SEM) was adopted to conduct tests of the measurement model and the main hypotheses represented in Figure 1. LISREL 8.80 (Jöreskog and Sörbom, 1993) was applied for data analysis in the current study. A survey instrument was designed and used to gather data for use in this study. Data were collected using an online survey administration tool (www.qualtrics.com). Findings: The results indicate that two dimensions of customer participation – information resource and codeveloper activities – demonstrate distinct impacts on customers' responses. Specifically, customer participation (information resource) is negatively related to customer shopping values and satisfaction. However, another dimension of customer participation (codeveloper activities) is positively related to the same outcomes. Originality/value: To the best of the authors' knowledge, this study is among the first to integrate customer participation and customer orientation to understand the phenomenon of customer co-creation. The study applies for a two-dimensional customer input construct and empirically tests their impacts on customer experience. Both utilitarian value and hedonic value are included in the research framework to assess customer value experience.